KESIAPAN PELAKSANAAN “DYNAMIC GOVERNANCE” DALAM PENINGKATAN KUALITAS PELAYANAN BADAN PENYELENGGARAAN JAMINAN SOSIAL (BPJS) KESEHATAN DI KANTOR LAYANAN OPERASIONAL KABUPATEN LEBAK PROVINSI BANTEN - Ayuning Budiati; Leo Agustino; Ahmad Mahdi; Nur Kemala Dewi (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2019)
According to some experts, Indonesia in addition to using the New Public Service paradigm also uses the dynamic governance paradigm in the delivery of its public services, for the sake of achieving better quality public services and public welfare. For this reason, a strategy is needed to prepare the implementation of dynamic governance properly, especially in the service of the Lebak Regency BPJS. There are several problems in BPJS services in Lebak Regency, first, supporting facilities for registration of BPJS health staff in Lebak Regency are still very minimal in supporting services for inputting data for prospective BPJS candidates, second, the online BPJS registration system often experiences obstacles in data verification because it always invalid, so prospective participants must come to the BPJS health office directly to register; third, the facilities and infrastructure provided in the waiting room for the BPJS health office are still very minimal, the number of seats available for potential participants is still inadequate, toilets are available available is only used for employees, and parking spaces provided for potential participants are very small and insufficient for many vehicles while BPJS participants who register online or directly must all do activation or exchange e-IDs with BPJS health card members to health offices nan BPJS health. And finally, the absence of Human Resources (HR) in accordance with expertise to provide services to answer and assist prospective participants by explaining information on filling in the health BPJS form, health BPJS registration requirements, and information regarding BPJS health membership in the BPJS health office. , it can be seen from the security officers who are supposed to be in charge of guarding the security, helping the prospective participants fill out the registration form. HR in the BPJS office is still very inadequate. The approach used is qualitative with the research method used is descriptive analytic, which seeks to describe and provide an explanation of the readiness of implementing "dynamic governance" in the implementation of BPJS in Lebak Regency. The results showed that the community felt the benefits of the Health BPJS even though there were still obstacles in their implementation. The limited access and range of services of the Health BPJS Lebak Regency is important to be an evaluation material so that it can be used as a strategy to improve BPJS services in the Lebak Regency in the context of readiness to face "dynamic governance".